Pliocene evolution of the tropical Atlantic thermocline depth - C. M. H. van der Weijst (Climate of the Past, 2022)
It has been hypothesized that global temperature trends are tightly linked to tropical thermocline depth, and that thermocline shoaling played a crucial role in the intensification of late Pliocene Northern Hemisphere glaciation. The Pliocene thermocline evolution in the Pacific Ocean is well documented and supports this hypothesis, but thermocline records from the tropical Atlantic Ocean are limited. We present new planktonic foraminiferal Mg/Ca<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="37pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="8d80044f3aec51e4692a94d1e9a6765c"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="cp-18-961-2022-ie00001.svg" width="37pt" height="14pt" src="cp-18-961-2022-ie00001.png"/></svg:svg>, δ18O, and δ13C records from the late Pliocene interval at Ocean Drilling Program Site 959 in the Eastern Equatorial Atlantic (EEA), which we use to reconstruct ocean temperatures and relative changes in salinity and thermocline depth. Data were generated using surface-dwelling Globigerinoides ruber and subsurface-dwelling Neogloboquadrina dutertrei. Reduced gradients between the surface and subsurface records indicate deepening of the EEA thermocline at the end of the mid-Piacenzian Warm Period (mPWP; ∼ 3.3–3.0 Ma). We connect our late Pliocene records to previously published early Pliocene δ18O data from Site 959 and compare these to the Site 1000 in the Caribbean Sea. Over the course of the Pliocene, thermocline changes in the EEA and Caribbean Sea follow similar patterns, with prominent step-wise thermocline deepening between ∼ 5.5 and 4.0 Ma and gradual shoaling up to the mPWP, followed by minor deepening at the end of the mPWP. The tropical thermocline depth evolution of the tropical Atlantic differs from the Pacific, which is characterized by gradual basin-wide shoaling across the Pliocene. These results potentially challenge the hypothesized link between tropical thermocline depth and global climate. The mechanisms behind the periodically divergent Pacific and Atlantic thermocline movements remain speculative. We suggest that they are related to basin geometry and heterogenous temperature evolutions in regions from where thermocline waters are sourced. A positive feedback loop between source region temperature and tropical cyclone activity may have amplified tropical thermocline adjustments.